Evaluation of microstructure and mechanical properties of annealed SLMed Ti–6Al–4V alloy using laser ultrasonics - Jiazheng Jiang; Yaoxin Huang; Anmin Yin; Yeqing He; Xiaodong Xu; Xuejun Yan; Ying Wang; Tingxiao Tang (Journal of Materials Research and Technology)
This paper investigates the relationship between the microstructure of annealed SLM Ti–6Al–4V alloy and ultrasonic eigenvalues. It proposes a mechanism for the interaction between the titanium alloy's microstructure and laser ultrasonic waves. Building on the enhanced Hall-Petch relationship that correlates grain size with mechanical properties, we establish and validate calculation models for yield strength, tensile strength, and hardness based on the ultrasonic time-domain attenuation coefficient, using experimental data for verification. The results indicate that the accuracy of the models linking microstructure and mechanical properties to ultrasonic eigenvalues is approximately 0.85.